PENGGUNAAN HORMON PERTUMBUHAN REKOMBINAN TERHADAP PERTUMBUHAN IKAN SELAIS (Ompok hypopthalmus) - Maulina Sawitri; Usman Muhammad Tang; Henni Syawal (Berkala Perikanan Terubuk, 2018)
This study was aimed to determine the best dose of recombinant growth hormone on the growth of selais fish (Ompok hypopthalmus). This study used a complete randomized desigh with one factor that is recombinant growth hormone dose and 3 repetition. The dose given were 0 mg/kg, 6 mg/kg, 12 mg/kg, 18 mg/kg and 24 mg/kg. The results showed that addition of rElGH at dose of 12 mg/kg were the best dose for selais fish growth’s parameters; absolute length growth (3,60± 0,6 cm), absolute weight growth (3,85 ± 0,46 g), daily growth rate (5,56 ± 0,32 %), food convertion ratio (1,10 ± 0,12), protein and fat retention (46,73 ± 21,34 % and 103,83 ± 21,43 %). The highest level of glycogen muscle (22,43 ± 0,61 mg/g) was found in addition of rElGH at dose of 18 mg/kg.